2011
DOI: 10.1021/ie102436u
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Switching of Monomer Additions for Controlling the Compositions and Microstructures of Segmented and Random Ethylene-Propylene Copolymers in Polypropylene in-Reactor Alloys

Abstract: International audienceThis work aims at shading fundamental insights into mechanisms that dictate the composition and microstructure of polypropylene/poly(ethylene-co-propylene) (PP/EPR) in-reactor alloys produced by the multizone circulating reactor (MZCR) technology, a novel one for polyolefin production. For this purpose, this technology is simulated by a batch process with periodic switching of monomer additions. An increase in the switch frequency leads to a decrease in the fraction of ethylene/propylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 20 publications
3
56
0
Order By: Relevance
“…Even in this latter case, these shells are so thin that segregation of different polymer phases is minimized. As expected, when the ASPP was used to prepare IPC in a previous work, 16 the size of the dispersed EPR phase domains decreased with increasing switching frequency (herein number of cycles). Furthermore, a large amount of EPS could be formed, owing to the fact that polymer particles were exposed to atmosphere "propylene" and atmosphere "ethylene-propylene" time and again.…”
Section: Atomsphere-switching Polymerization Processsupporting
confidence: 82%
See 1 more Smart Citation
“…Even in this latter case, these shells are so thin that segregation of different polymer phases is minimized. As expected, when the ASPP was used to prepare IPC in a previous work, 16 the size of the dispersed EPR phase domains decreased with increasing switching frequency (herein number of cycles). Furthermore, a large amount of EPS could be formed, owing to the fact that polymer particles were exposed to atmosphere "propylene" and atmosphere "ethylene-propylene" time and again.…”
Section: Atomsphere-switching Polymerization Processsupporting
confidence: 82%
“…It relies on periodic switching of monomers which can improve the compatibility between EPR and PP by controlling the molecular structures of the EPS. 16,17 Unlike a conventional TSPP in which the homopolymerization of propylene and the copolymerization of ethylene and propylene take place successively and only once, in the case of ASPP they proceed periodically and many times.…”
mentioning
confidence: 99%
“…[4][5][6][7] Among several techniques, in situ copolymerization with ethylene by adding a gas-phase reactor in the production line is an effective one which has been used on an industrial scale to obtain highimpact resistant PP or impact PP copolymer (IPC). 13,14 When IPC is melted, a unique heterophasic morphology is formed. EP random copolymer (EPR) is a major component which is responsible for the toughness improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Referring to works published by Tien et al . their sEP was obtained by fractionation, C7‐soluble fraction, which corresponds to the cEP in this present work . However, in strictly defining, sEP should be referred to the copolymers with the segments of long sequences of either ethylene (E) or propylene (P) units, or both types of segments in the chain.…”
Section: Introductionmentioning
confidence: 93%
“…The periodic‐switching technique was exploited to manipulate the EPR and sEP contents. The results showed that the droplet size of the EPR dispersed phase decreased as the content of the sEP increased . This suggested the role of the sEP on the improvement of the interfacial adhesion between hPP and EPR phases, and this similar finding also has been reported in several works .…”
Section: Introductionmentioning
confidence: 99%